The impact of exercise training on basal BDNF in athletic adolescents - Kim, Young Il (J Phys Ther Sci, 2016)
[Purpose] The purpose of this study was to investigate the impact of exercise training on basal brain-derived neurotrophic factor in athletic adolescents. [Subjects and Methods] Twenty-two male adolescents participated in this study. The subjects were divided into a control group (n=9) and trained group (n=13). The trained group comprised table tennis athletes with more than 3 years of training who regularly exercised 18 hours per week. [Results] The results of this study show the trained group had significantly lower basal brain-derived neurotrophic factor levels than the control group. Further, platelet levels were significantly higher in the trained group than in the control group. However, no significant differences were observed between the groups in serum nerve growth factor level or physical characteristics (body weight, body mass index, fasting blood glucose). [Conclusion] This study showed that the basal brain-derived neurotrophic factor level of well-trained athletic adolescents was lower than that of the control group. Further research with a larger sample size is required to confirm the finding that lower basal brain-derived neurotrophic factor levels are associated with long-term habitual exercise in athletic adolescents.